2014
DOI: 10.1007/s10103-014-1586-4
|View full text |Cite
|
Sign up to set email alerts
|

“Low-intensity laser therapy effect on the recovery of traumatic spinal cord injury”

Abstract: Scientific advances have been made to optimize the healing process in spinal cord injury. Studies have been developed to obtain effective treatments in controlling the secondary injury that occurs after spinal cord injury, which substantially changes the prognosis. Low-intensity laser therapy (LILT) has been applied in neuroscience due to its anti-inflammatory effects on biological tissue in the repairing process. Few studies have been made associating LILT to the spinal cord injury. The objective of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 49 publications
1
26
1
9
Order By: Relevance
“…Epidemiological studies on traumatic SCI (TSCI) are regularly conducted worldwide; however, these studies are less common in China (2). The male to female ratio ranges between 2.5:1 and 6:1, and as average life expectancy increases the incidence increases every year in China (3).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies on traumatic SCI (TSCI) are regularly conducted worldwide; however, these studies are less common in China (2). The male to female ratio ranges between 2.5:1 and 6:1, and as average life expectancy increases the incidence increases every year in China (3).…”
Section: Introductionmentioning
confidence: 99%
“…Avaliou-se o comportamento axonal por microscopia de fluorescência e a recuperação funcional por análise das pegadas (grupo hemissecção) e escala BBB (Basso--Beattie-Bresnahan; grupo contusão). O comprimento avaliados após lesão traumática (T9-T10) em 31 ratos wistar 4 , divididos em 5 grupos: grupo C -grupo controle sem cirurgia (n: 3); grupo CC -grupo controle com cirurgia, mas sem LM (n: 3); grupo ML -grupo LM sem laser (n:5); grupo LA -grupo laser 6h após a cirurgia sem LM (n: 5); grupo LB -grupo laser 48h após a cirurgia sem ML (n: 5); grupo MLA -grupo LM + laser 6h após cirurgia (n: 5); grupo MLB -grupo LM + laser 48h após cirurgia (n: 5). A cirurgia foi uma laminectomia (T8-12) sem lesão do saco dural, a LM foi promovida utilizando a mesma metodologia do estudo acima, após o procedimento a pele foi suturada.…”
Section: Resultsunclassified
“…A TLBI pode promover uma resposta anti-inflamatória por meio de um mecanismo que envolve a inibição de ácido araquidônico, reduzindo assim a expressão da ciclooxigenase (COX-2) e diminuindo a produção de PGE2, além de fatores de modulação ligados ao ácido ribonucléico (mRNA) de citocinas proinflamatórias 4 . Por isso, a TLBI pode atenuar a lesão secundária presente na LM traumática, possibilitando um melhor prognósti-co 7,15,18 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In recent years, PBM has been broadly applied in therapy for brain injury and other cerebral diseases such as stroke and neurodegenerative disorders, where it has yielded encouraging results . Similarly, research on SCI has revealed that PBM can suppress the activation of immune cells at the site of injury, reduce the expression of proinflammatory factors and chemokines and reduce the incidence of secondary SCI, as well as promote the large‐scale regrowth of nerve fibers at the site of injury and significantly improve the recovery of locomotor function . Previously, we discovered that irradiating SCI sites by percutaneous in rats with near‐infrared light at 810 nm, 150 mW, 1500 J/cm 2 can promote macrophage polarization from the M1 to the M2 phenotype, reduce the immunoinflammatory response, promote the survival of neurons and improve the recovery of locomotor function .…”
Section: Introductionmentioning
confidence: 99%